ISOLATION OF AN ENDOGENOUS GROWTH REGULATOR FROM AGRICULTURAL CROPS - Nuraly, A. M.; Mutushev, A. Zh.; Rysbayeva, Y. Zh.; Akhmetova, A. B.; Seisenova, A. B. (ЗКАТУ им. Жангир хана, 2024)
This article explores the use of biological products with growth-stimulating and immunomodulatory effects in agricultural practice, focusing on the production and influence of growth regulators on grain crops, specifically the high-grade winter wheat variety Steklovidnaya-24 from KazNIIZiR. The study aims to develop an endogenous growth regulator and assess its impact on grain crops. Phytohormones, as endogenous growth regulators, play a crucial role in plant growth and development, controlling various physiological and morphogenetic programs. The research involves obtaining growth regulators from cereal crops, with a particular focus on the cytokinin N6- benzylaminopurine (6-BAP). The experiments, conducted under hydroponic conditions, reveal the positive influence of growth regulators on seed germination and biometric indicators, such as increased linear dimensions and root system volume. The results demonstrate that the 1% concentrated solution of wheat extract with 6-BAP exhibited the highest germination rate, showcasing its potential as an effective growth regulator for winter wheat seeds. Overall, the study emphasizes the importance of natural growth regulators for sustainable agricultural practices and highlights the specific impact of cytokinins on seed germination and plant growth.
Nuraly, A. M. Іsolation of an endogenous growth regulator from agricultural crops / A. M. Nuraly, A. Zh. Mutushev, Y. Zh. Rysbayeva, A. B. Akhmetova, A. B. Seisenova. - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2024. - 2-2 (75). Б. ІІ. - Р. 32-39.
Keywords: Phytohormone; 6-BAP; auxin; gibberellin; cytokinin; ethylene; photosynthesis; научный журнал; зкату